Studies on certain attributes of buffalo follicular fluid - DAS, G K; AGARWAL, S K; PATHAK, M K; SINGH, S K; SHANKER, UMA (The Indian Journal of Animal Reproduction, 2005)
The aim of the present investigation was to determine average yield of follicular fluid, total protein, estradiol andprogesterone profile in the follicular fluid of buffalo ovaries. The follicular fluid was collected by aspirating the visible surfacefollicles. The average yield of buffalo follicular fluid (buFF) per ovary was 0.45±0.03 ml which was higher during the months betweenNovember to March (0.54±0.02 ml) than April to September (0.38±0.02 ml). The mean concentration of total protein in pooledbuFF samples was 4.86±0.41 g% (ranged between 3.0 to 6.7 g%). The mean concentration of estradiol and progesterone in pooledbuFF samples were 3044.99±31.85 pg/ml and 74.31±2.94 ng/rnl, respectively.
Keywords: Buffalo; follicular fluid; yield; protein; steroid